THE IMPACT OF CAPITAL BUDGETING AND ITS REALIZATION ON ACCOUNTABILITY AND BUDGET PERFORMANCE AT THE BANJARMASIN CITY HOUSING AND SETTLEMENT DEPARTMENT - Iskandar , Dahliana (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The objective of this study is to examine and analyze the influence of Capital Budgeting and Capital Budget Realization on Accountability and Budget Performance at the Housing and Settlement Department of Banjarmasin City. This is a quantitative study using a saturated sampling technique, in which the sample size is equal to the population, totaling 57 employees consisting of Civil Servants (PNS), Government Employees with Work Agreements (P3K), and individual consultants at the Housing and Settlement Department of Banjarmasin City. The method used in this study is path analysis, and the data were processed using SmartPLS version 3.2.9. Based on the results and discussion, several conclusions were drawn: Capital Budgeting influences accountability at the Housing and Settlement Department of Banjarmasin City. Budget realization affects accountability at the same department. Capital Budgeting influences budget performance. Budget realization affects budget performance. Accountability has an impact on budget performance. Accountability mediates the effect of Capital Budgeting on budget performance. Accountability also mediates the effect of budget realization on budget performance.